THE RISKS OF AREN SUGAR PROCESSING BUSINESS IN KOLAKA DISTRICT SOUTH EAST SULAWESI - Weka Gusmiarty Abdullah; Usman Rianse; Marsuki Iswandi; Sitti Aida A Taridala; Weka Widayati; Ine Fausayana; Lukman Yunus; M Arif Dirgantoro (International Journal of Sustainable Tropical Agricultural Sciences (IJSTAS), 2015)
AbstractBusiness of aren sugar processing intends to providing alternative sweetener source to fulfill sugar demand for community. Nonetheless, every business has a risk particularly agricultural product in general, including aren sugar processing business in which the raw resources were obtained from aren.The purpose of this research was to analyze the type and stage of risk related to aren sugar processing business in Kolaka District. Simple random sampling method was used to decide sample on this research. Quantitative descriptive analysis and coefficient of variance was used to analyze types and stages of risk in aren sugar processing business. The result of the research showed that there are six type risks on the extraction process, five type risks on aren cooking process, and one type risk on marketing. Risk types which have quantification value is analyzed for its risk stages, including raw material risk, production risk and price risk. Raw material risk had the highest stage of risk among other risks. Authority for endorsing continuity and development of aren sugar processing business was a based-risk development strategy, especially for raw material risk, as well as mentoring of production risk and marketing management.Keywords. risk, profit, aren sugar processing business